2020
DOI: 10.1021/acs.chemmater.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Two-Step Formation Pathway of Cs4PbBr6 Nanocrystals

Abstract: All-inorganic cesium lead halide perovskites have received much attention, but the study of the formation pathway is relatively little. We report here a new one-step approach for the synthesis of Cs 4 PbBr 6 nanocrystals (NCs), as well as the exploration of its formation process. Mixing three independent precursors of Cs, Pb, and Br in a cuvette, we monitor the evolution of Cs 4 PbBr 6 NCs by in situ absorption spectroscopy, the formation of which features a sharp absorption peak at 313 nm. Based on this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…The microemulsion method has been used to obtain other inorganic perovskite NCs with different dimensionalities (CsPbBr 3 and CsPb 2 Br 5 ), as well as the ligand-free highly emissive Cs 4 PbBr 6 NCs . Recently, Hui et al reported a one-step method for the synthesis of Cs 4 PbBr 6 NCs by mixing three independent precursors of Cs, Pb, and Br in a cuvette . They proposed a two-step pathway for forming Cs 4 PbBr 6 NCs.…”
Section: D Non-perovskite (Perovskite Derivative) Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microemulsion method has been used to obtain other inorganic perovskite NCs with different dimensionalities (CsPbBr 3 and CsPb 2 Br 5 ), as well as the ligand-free highly emissive Cs 4 PbBr 6 NCs . Recently, Hui et al reported a one-step method for the synthesis of Cs 4 PbBr 6 NCs by mixing three independent precursors of Cs, Pb, and Br in a cuvette . They proposed a two-step pathway for forming Cs 4 PbBr 6 NCs.…”
Section: D Non-perovskite (Perovskite Derivative) Ncsmentioning
confidence: 99%
“…418 Recently, Hui et al reported a onestep method for the synthesis of Cs 4 PbBr 6 NCs by mixing three independent precursors of Cs, Pb, and Br in a cuvette. 419 They proposed a two-step pathway for forming Cs 37b). 421 The evolution of the normalized absorbance at these two spectral positions had the inverse dependence on the OLA concentration.…”
Section: D Non-perovskite (Perovskite Derivative) Ncsmentioning
confidence: 99%
“…The sample using fresh metal-oleate precursor possesses three absorption peaks which are ascribed to the exciton absorption peaks of CsPbBr 3 , [PbBr 4 ] 2− , and Cs 4 PbBr 6 , respectively. 25 The photoluminescence (PL) peak shows a large full-width-athalf-maximum (fwhm = 29 nm) and low luminescent intensity. After aging the metal-oleate precursors for 4 months, the exciton absorption peaks of [PbBr 4 ] 2− and Cs 4 PbBr 6 disappear and the CsPbBr 3 exciton absorption peak is enhanced, accompanied by a narrower and stronger PL emission peak.…”
Section: T H Imentioning
confidence: 99%
“…1). We hypothesized that the conventional approach -referred to as oleylamine -oleic acid (OLAM/OA) path 1 -suffers from the immediate conversion of the PbBr2 into haloplumbate ionic solute (PbBr3 -) upon the action of OLAM/OA 38,39 . The subsequent reaction with injected Cs-ions is thus quantitative and fast, and hence nucleation and growth are not temporally separated.…”
Section: Synthesis Of Monodisperse Cspbbr3 Qdsmentioning
confidence: 99%
“…Only upon the injection of Cs-DOPA, does the PbBr3appear on the course of 100 ms, evidenced as an additional peak emerging at lower energies (3.85 eV) (Supplementary Fig. 21), owing to the formation of a PbBr3complex 39,49 .Once the accumulation of PbBr3surpasses a nucleation threshold (supersaturation), CsPbBr3 QDs form (on the order of seconds, Fig. 3b).…”
Section: Reaction Mechanismmentioning
confidence: 99%